Outdoor performance of the black globe temperature sensor on a hot and humid tropical region - ACERO, Juan A. (Institutional Knowledge at Singapore Management University, 2023)
A crucial variable to evaluate thermal comfort is the mean radiant temperature (Tmrt). In this paper we evaluate the performance of the 150 mm black globe thermometer to provide reliable Tmrt values for outdoor settings in Singapore. Accurate Tmrt values are calculated by the method of integral radiation measurements. Based on these, the mean convection coefficient of the black globe has been re-calibrated. Results show an improvement in the estimation of Tmrt with the new coefficient in comparison with the default version suggested in ISO7726:1998. Increasing the averaging periods of the measured variables improved the performance of the derived mean convective coefficients to estimate Tmrt. During clear skies day and for 10-min averaged data, RMSE for Tmrt reduce to 3.9 °C (7.4 °C for ISO7726:1998 coefficient) with an overestimation on high incoming solar radiation periods and an underestimation during the morning and evening (low solar elevation). During overcast dry conditions an underestimation of Tmrt is also expected which is higher in the rain/wet periods. The mean convective coefficient presented in this work can provide improved estimations of Tmrt relevant for outdoor thermal comfort studies in hot and humid tropical climates like Singapore.